Attitudes Toward and Acceptability of Medical Marijuana Use Among Head and Neck Cancer Patients. (January 2023) - Levin, Marc; Zhang, Han; Gupta, Michael K.
Objective: This study aims to understand the attitudes toward marijuana in HNC patients. Methods: A 17-question questionnaire regarding medical marijuana (MM) was distributed to HNC patients at a tertiary cancer center. Results: 63 HNC patients completed the questionnaire. Patients that had used or were using marijuana described benefit with symptoms of headache, pain, nausea, and loss of appetite. 83% of all patients considered marijuana as treatment for cancer related pain and 67% as treatment for cancer related anxiety. About 70% of patients actively undergoing cancer treatment believed marijuana medications would help with symptoms during treatment. Conclusions: By understanding how HNC patients perceive MM, HNC teams may be able to prescribe and educate their patients on MM.